Implementation of The Five Pillars Diabetes Education on Knowledge and Self-Care Behavior Among Patients With Type 2 Diabetes - Fiolenty Sitorus; Putri Valerie Gaudiosa Noija; Wulan Patricia Nikita Pusung; Renova O. Br. Sibuea (International Journal of Health and Pharmaceutical (IJHP), 2026)
Type 2 diabetes mellitus (T2DM) management requires effective self-care, which can be strengthened through structured education. The Five Pillars of Diabetes Self-Care including nutrition, physical activity, medication adherence, blood glucose monitoring, and foot care provide a comprehensive framework for patient with T2DM. This study evaluated the effects of an educational program based on these five pillars on the knowledge and self-care behaviors of patients with T2DM. A quasi-experimental one-group pretest–posttest design was used. A total of 24 patients with T2DM from the Jalan Emas Community Health Center in Tangerang were recruited using accidental sampling. The intervention consisted of four weekly interactive educational sessions that covered all five pillars. Valid and reliable instruments (the Five Pillars Knowledge Questionnaire and the Summary of Diabetes Self-Care Activities/ SDSCA) were used for data collection. Data were analyzed using the Wilcoxon Signed-Rank Test. Post-intervention analysis showed significant improvements in knowledge related to nutrition management (p = 0.023), blood glucose monitoring (p = 0.008), and foot care (p = 0.003). Overall self-care behavior also increased significantly (p = 0.001). However, no significant improvements were observed in knowledge related to physical activity (p = 0.317) and antidiabetic medication (p = 0.053). The Five Pillars Diabetes Education program was effective in improving key areas of knowledge and self-care behavior among patients with T2DM. These findings support the adoption of structured, comprehensive, and practical educational interventions, while also emphasizing the need for more targeted strategies to enhance physical activity engagement and medication adherence.